Deep brain stimulation of the subthalamic nucleus: effectiveness in advanced Parkinson's disease patients previously reliant on apomorphine. Issue 2 (1st February 2003) - Varma, T R K; Fox, S H; Eldridge, P R; Littlechild, P; Byrne, P; Forster, A; Marshall, A; Cameron, H; McIver, K; Fletcher, N; Steiger, M
Abstract : Objectives: To assess the efficacy of bilateral subthalamic nucleus (STN) deep brain stimulation (DBS) in patients with advanced Parkinson's disease previously reliant on apomorphine as their main antiparkinsonian medication. Methods: Seven patients with motor fluctuations despite optimal medical treatment given as predominantly apomorphine infusion (n=6), or intermittent apomorphine injections (n=1) underwent bilateral STN DBS using frameless stereotactic surgery. Standard assessments of parkinsonism and motor fluctuations, using Unified Parkinson's Disease Rating Scale (UPDRS) were performed before and six months after surgery. Assessments were performed both on and off medication, and postoperative with the stimulators switched on and off. Results: Bilateral STN DBS improved motor scores (UPDRS III) by 61% when off medication (p<0.05). Clinical fluctuations (UPDRS IV items 36–39) were reduced by 46.2% (p<0.05). Total daily apomorphine dose was reduced by 68.9% (p<0.05) and apomorphine infusion via a pump was no longer required in four patients. There were no operative complications. Two patients required treatment for hallucinations postoperatively but there was no significant change in mini-mental state examination. Conclusions: In patients with advanced Parkinson's disease, previously reliant on apomorphine, bilateral STN DBS is an effective treatment to reduce motor fluctuations and enable a reduction in apomorphine use.